KONSEP SYUKUR DALAM AL-QUR’AN DAN APLIKASINYASAAT MEMASUKI RUMAH BARU - Dahliati Simanjuntak (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2024)
In Qur'anic studies, gratitude is the opposite of kufr. Kufr is defined as closing oneself off, while gratitude is defined as opening up or acknowledging oneself. Gratitude is part of the Islamic teaching of “gratitude” which is important and highly regarded in the eyes of Allah as well as for humans. The positive effects of gratitude are thought to make poor people rich and sad people happy. However, in practice, there are still many people who have not practiced the teachings of gratitude to the fullest in their lives. This is allegedly because many people do not understand how the application of gratitude itself. Many misuse the favors that are given to things that are not in accordance with the application of gratitude. Therefore, this paper focuses more on the discussion of how the application of gratitude towards Allah's blessings by using it for good things. It aims to describe and analyze the meanings of the Qur'anic verses and the nature of gratitude in the Qur'anic perspective, besides its target towards Muslims through its implementation in life, considering the context of gratitude is the expression and action of humans for the grace of Allah SWT. which is sometimes difficult to implement. This paper also presents the importance of reconstructing the human self as a forgetful creature (kufr nikmat) so that it is worth reading in the treasures of Islamic science. The method of this writing is library research, which examines normative sources that can be used as informative presentations in the context of human life (Muslims) at large. Therefore, the reconstruction of the human self is important to realize oneself in the form of gratitude with the heart, gratitude with the tongue, gratitude through deeds for all forms of gifts (favors/graces) in every dimension of one's life/Muslims. This paper aims to describe and analyze the meanings of the Qur'anic verses and the nature of gratitude in the Qur'anic perspective, in addition to its target for Muslims through its implementation in life.